Empirical Study on Factors Related Attitudes on Fast-Food Consumption among University Students in Malaysia - Lu Man Hong; Kang Yee Ming (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
Fast food is a type of cuisine that may be swiftly made and offered to customers at a low cost. Time by time, changes in client demand, such as taste and lifestyle, may be detected, leading to the launch of several new menus by fast food companies to meet customer desire. This has an impact on the attitudes of university students on fast food eating during the period. The purpose of this study is to look at the link between flavour, time savings, and promotion attractiveness, towards university students' attitude about fast food intake. A study comprising 384 respondents from Malaysian colleges was done utilising online questionnaires using Google Form. All data was proceeded by SPSS software 26.0. The findings revealed that the three independent variables are significantly related to dependent variable. This study can help researchers to find out more about fast food and the information provided can be used as reference material in the future.